Habilidades Sociales en las Familias de los Estudiantes del Colegio Nacional “Chambo”Chambo. Octubre 2017 – Marzo 2018 - Villa Cuji, Cristhian Fabian (2018)
The purpose of this research project was to determine the development of social skills in the families of the 10th grade students of the parallel "A" Basic General Education of the Chambo School, which are of great importance within the social and family development in the students, social skills are the specific social behaviors or techniques that allow to act more effectively in interpersonal relationships, noting that social skills are not personality traits but acquired and innate behaviors and therefore susceptible to learning and training. The methodology used was for the non-experimental design, for the type of cross-sectional study and for the correlational level, the population was the students of the National School "CHAMBO", the sample was not probabilistic and intentional the thirty four students were worked from the selected institutions, the techniques used were psychometric tests, the instruments used were the Goldstein social skills checklist and the "FES" social family scale, students presented medium and high levels around their social skills, while the level of development of the family social climate is inadequate because when anybody has a family problem, they do not always help each other to solve it.